Geographic dependency of identity-associated data. (2nd October 2018) - Djerasimović, Petar
ABSTRACT: A consequence of the proliferation of private and identity data in a globalized world is the emergence of geographically dependent data representations – data in various systems in the world cannot always be captured and processed in the exact same form and individuals often transform data they are making available to systems so it would conform with locally used scripts, languages or constraining rules. Data representation as well as semantics of that data may vary across language and state domains and subjects associated with that data may in different locations be granted different rights stemming from that data. Current systems are mostly built on an attribute-based model of identity and we propose extending this model to include this naturally occurring dependency. Analysing some of the most popular protocols and standards for identity management in current use we have grouped frequently used identity attributes according to their geographic dependency to illustrate what kind of geographic dependencies can be found. We argue for a simple model where data representation and semantics are dependent of the geographic location of data interpretation. Also, we provide an example of extending an existing protocol of identity data exchange with the introduced geographic aspects.